Operational Practices and Related Issues Regarding Intellectual Property Education and Training at Selected Universities in Zimbabwe - Ngwenya , Sibongile; Onyancha, Omwoyo Bosire (International Journal of African Higher Education, 2025)
The quality of an Intellectual Property (IP) educational programme largely depends on the level of experience and interest of the IP educator. However, in most universities in Zimbabwe there seems to be operational glitches since IP education and training is conducted in diﬀerent disciplines and mostly by staﬀ without practical skills nor prior technical background in IP. The study sought to investigate the operational practices in relation to IP education and training within the universities. A survey of four universities was carried out with a sample of lecturers (692), research ofcers (4), IP ofcer (1), and faculty librarians (4). Questionnaires were administered to the lecturers while interviews were administered to the IP ofcer, research ofcers and faculty librarians. The questionnaire response rate was 52.9% (366 lecturers) while all the nine selected participants were interviewed. The results indicated that 147 (40%) lecturers were unaware of departments responsible for IP education and training within their universities. The interview results suggested that the IP ofce, the library, the research ofce and teaching departments were responsible for IP education and training in the universities.